Reappraisal of lignocaine therapy in management of myocardial infarction. - Pentecost, B L (1981)
The use of lignocaine in the prevention of ventricular fibrillation among patients admitted to a coronary care unit has been reviewed over the 12-year period 1967 to 1978 inclusive. The practice of suppressing warning ventricular ectopic activity has gradually been abandoned with the result that whereas in 1967 to 1968 33 per cent of all patients received lignocaine therapy, in 1972 to 1973 the number had fallen to 15 per cent, and in 1977 to 1978 to 4 per cent. The incidence of ventricular fibrillation was not significantly changed at 9.1, 7.7, and 7.8 per cent, respectively. Approximately 80 per cent of all patients suffering ventricular fibrillation within the coronary care unit were initially resuscitated and approximately 50 per cent survived hospital admission. Death was rarely a result of recurrent ventricular fibrillation and for the most part took the form of pump failure or late unexpected death. Experience suggests that the use of lignocaine to suppress ventricular ectopic activity observed in the first few hours of admission to hospital with acute myocardial infarction has no therapeutic value.